Acupuncture Point "Hegu" (LI4) Is Close to the Vascular Branch from the Superficial Branch of the Radial Nerve. (25th June 2019) - Umemoto, Kanae; Naito, Munekazu; Tano, Kaori; Terayama, Hayato; Koike, Taro; Ohmichi, Mika; Ohmichi, Yusuke; Sakabe, Kou; Nakano, Takashi
Abstract : The acupuncture point "Hegu" (LI4) has been used for treating peripheral circulatory failure, which is located in the area covered by the superficial branch of the radial nerve (SBRN). SBRN has branches reaching arteries, so-called vascular branches (VBs), which are thought to be involved in the arterial constriction. The distribution areas of the VBs from the SBRN have been reported, but the positional relationship between these distribution areas and the acupuncture points are not known. To examine the positional relationship between LI4 and VBs from the SBRN, forty hands were examined to assess the positional relationship between the acupuncture points "Erjian" (LI2), "Sanjian" (LI3), LI4, and "Yangxi" (LI5) in the Yangming Large Intestine Meridian of Hand, which are located in the area covered by SBRN, and the VBs from the SBRN. After the VBs were identified, the distances from the acupuncture points (LI2, LI3, LI4, and LI5) to the point where the VBs reached the radial artery or the first dorsal metacarpal artery were measured. VBs reaching the radial arteries were observed in all specimens. The mean distances from LI2, LI3, LI4, and LI5 to the point where the VBs reached the radial artery were 64.2 ± 8.2 mm, 42.0 ± 7.5 mm, 4.3 ± 4.3 mm, and 33.0 ± 4.8 mm, respectively. LI4 was significantly closer than the other acupuncture points (P<0.01). The nerve fibers of the VBs adjacent to the radial artery were confirmed using hematoxylin and eosin staining. Our findings provide anatomical evidence that stimulation at LI4 is used for treating peripheral circulatory failure such as Raynaud's disease. LI4 is significant because it is located at a source point, making it clinically important.